Examine the relationship between information technology acceptances and employees’ task performance: a study at Holcim (Malaysia) Sdn Bhd - Mohd Khalid, Mohammad Syafiq (2012)
The report is about the study on the relationship between Information Technology Acceptance with Employees’ Task Performance at Holcim (Malaysia) Sdn Bhd. This report is created by refer the result that I got from surveys of giving out from questionnaire to the staffs in the Holcim (Malaysia) Sdn Bhd at City Square (Corporate Office) and Pasir Gudang Plant as my respondents in this research. The questionnaire was distributed to 100 respondents which are registered employee at Holcim (Malaysia) Sdn Bhd in order to get useful information and accurate data regarding the relationship between Information Technology Acceptance with Employees’ Task Performance. This study found that there is no relationship between perceived ease of use with the employees’ task performance. Secondly, the researcher found that the quality of information technology have a relationship with the employees task performance. The researcher suggests to improve and increase the training program for employees because the information technology changes will influence the employees’ task performance to become poor. Besides that, researcher also suggest the company should always updating the quality of information technology because the good quality of the information technology give a good impact for employees and directly improve the company performance.